The Relationship between the Habit of Listening to Music using Earphones with the Incidence of Hearing Loss in Students of SMA Negeri 8 Luwu Timur 2023 - Rahman, Nilam Cahya; Sanna A, Andi Tenri; Lantara, A. Millaty Halifah Dirgahayu; Sulaiman, Andi Baso; Pratama, Ahmad Ardhani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The influence of music on modern life is evident through the widespread use of earphones, which is particularly popular among teenagers. While offering convenience for listening to music in various situations, the use of earphones is also linked to the risk of Noise-Induced Hearing Loss (NIHL). Earphones generate high noise intensity, reaching levels that can damage hearing, especially when used for extended periods. Global data from the World Health Organization (WHO) indicates a high prevalence of hearing loss, and Indonesia is among the countries with a significant prevalence. The type of research used is observational analytic using a cross-sectional study approach. Determination of the number of samples in this study was by total sampling technique. Univariate data analysis is presented in the form of frequency distribution and percentage and bivariate analysis using the Chi Square test and data processing using the computerized SPSS version 16.0 program. There is a significant relationship between the use of earphones and hearing loss in students of SMA Negeri 8 Luwu Timur.